Thermodynamic Inversion Origin of Living Systems - Kompanichenko, Vladimir N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book discusses the theory, general principles, and energy source conditions allowing for the emergence of life in planetary systems. The author examines the material conditions found in natural hydrothermal sites, the appropriate analogs of prebiotic environments on early Earth. He provides an overview of current laboratory experiments in prebiotic materials chemistry and substantiation of a new direction for the experiments in the origin of life field. Describes thermodynamic inversion and how it relates to the living cell; Examines the current direction of experiments on prebiotic materials chemistry; Introduces and substantiates necessary conditions for the emergence of life.
Astrobiology: Approaches to the Origin of Life on Earth and Beyond -- Part I. Life and a Principal Way of Its Origin in the Universe -- General Thermodynamic Characteristics of Living Systems -- Principal Way of Life Origin in the Universe -- General Characteristics of the Origin-of-life Medium -- Part II. Origin of Initial Living Systems on Early Earth -- Irreversible Prebiotic Evolution in Hydrothermal Systems -- Exchange of Information During Prebiotic Evolution -- Origin of Primary Living Systems on Earth in Course of Thermodynamic Inversion -- Part III. Kamchatka Geothermal Region AS A Testing Ground for Investigation OF THE Origin-of-Life Process -- Hydrothermal Systems in Kamchatka Peninsula and the Adjoining Region: Geological and Hydrochemical Characteristics -- Changeability of Pressure, Temperature and Concentrations of Components in the Explored Hydrothermal Systems -- Organic Matter in the Hydrothermal Systems of Kamchatka Peninsula and Nearby Area.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Chemistry, Organic; Electric power production; Astrobiology; Biomaterials; Engineering Thermodynamics, Heat and Mass Transfer; Organic Chemistry; Electrical Power Engineering; Mechanical Power Engineering; Astrobiology; Biomaterials